Knowledge, attitudes, beliefs, and health behaviors of bone health among Caribbean Hispanic/Latino adults - Noel, Sabrina E. (Arch Osteoporos, 2019)
SUMMARY: Few studies have examined knowledge and perceptions of osteoporosis among Caribbean Latino adults. Confusion regarding the term osteoporosis was noted. Doctors were viewed as trusted sources of health information, although descriptions of a paradoxical relationship emerged. This study can be used to inform culturally tailored interventions for osteoporosis prevention. PURPOSE: The overall goal of this study was to assess knowledge, attitudes, and beliefs of bone health and osteoporosis among Caribbean Latino adults aged ≥ 50 years. METHODS: This triangulated mixed methods study included completion of a quantitative questionnaire and participation in one of four focus groups to obtain information on (1) general health, (2) knowledge about bone health and osteoporosis, (3) sources of information about bone health, and (4) prevention knowledge and personal responsibility. Quantitative data were analyzed using SAS, and qualitative data were analyzed using descriptive and structural coding by two independent research members. RESULTS: The majority of participants were female (73%), Dominican (84%), and low income (82% < $20,000) with a mean age of 68.4 (± 8.5) years. Most participants had heard of osteoporosis (90%); however, the majority were not able to accurately describe this chronic condition. Health care providers were viewed as most trusted sources of health information, despite feelings of being rushed during their visits, with limited communication about preventative care. Most participants felt that nutrition and exercise were important for overall health. CONCLUSIONS: Caribbean Hispanic adults in this study reported knowledge of osteoporosis and nutritional factors associated with prevention of this chronic condition. However, qualitatively, there was confusion between osteoporosis and other bone and joint conditions. Culturally specific interventions to promote prevention of osteoporosis are urgently needed for this underserved, high-risk population.